Economic Burden of Diabetic Mellitus Among Patients on Follow-up Care in Hospitals of Southwest Shewa Zone, Central Ethiopia - Addisu Bogale Zawudie; Dawit Wolde Daka; Dejene Teshome; Meskerem Seboka Ergiba (BMC, 2022)
Abstract Background Diabetes has emerged as one of the most serious health issues of the twenty-first century. Diabetes and its complications expose individuals and their families to catastrophic healthcare costs, which have a severe impact on the country's economy. Though the prevalence of diabetes is rising quicker in Ethiopia, little is known about its economic impact. Hence, this study aimed to determine the total cost of diabetic mellitus and associated factors among patients attending hospitals in Southwest Shewa zone, Central Ethiopia. Methods The study was conducted among diabetes patients who were on care and treatment from September to October 2020. Direct costs were calculated using the micro-costing technique, while indirect costs were calculated using the human capital approach. The statistical significance of cost difference between the groups of patient characteristics was determined using Wilcoxon and Kruskal-Wallis mean rank sum tests, and the factors associated with a total cost of illness were identified with Generalized Linear Model (GLM). Results Out of the planned patients, 398 have responded and were included in the analysis; making a response rate of 98.5%. The mean monthly total cost of diabetic mellitus was US$ 37.7(95% CI, 23.45-51.95). Direct and indirect costs constituted 76.2% and 23.8% of the total cost, respectively. The mean direct and indirect cost of diabetic mellitus per patient per month was US$ 28.73(95% CI, 17.17-40.29) and US$ 9.50 (95% CI, 1.99-16.99) respectively. Statistical mean cost differences were observed by gender, age groups, family size, and comorbidities. The total cost of illness was associated with residence (p=0.007), family size (p=0.001), presence of co-morbidities (p=0.04), and history of ever-stopping treatments (p<0.0001). Conclusions The total cost of diabetes condition was relatively high compared to other related literatures. The medical expenditures accounted for most direct costs for diabetic patients. As a result, the government should provide sufficient resources to safeguard patients against catastrophic medical costs. Efforts should be made to enhance access to diabetes care, and the supply of diabetic medications at all levels of health facilities.